Solve for y y^2-16y+64=0

Math
y2-16y+64=0
Factor using the perfect square rule.
Tap for more steps…
Rewrite 64 as 82.
y2-16y+82=0
Check the middle term by multiplying 2ab and compare this result with the middle term in the original expression.
2ab=2⋅y⋅-8
Simplify.
2ab=-16y
Factor using the perfect square trinomial rule a2-2ab+b2=(a-b)2, where a=y and b=-8.
(y-8)2=0
(y-8)2=0
Set the y-8 equal to 0.
y-8=0
Add 8 to both sides of the equation.
y=8
Solve for y y^2-16y+64=0

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top